Jump to navigation Jump to search

General

Display information for equation id:math.28352.7 on revision:28352

* Page found: Hua's identity (eq math.28352.7)

(force rerendering)

Cannot find the equation data in the database. Fetching from revision text.

Occurrences on the following pages:

Hash: 2e4075d194151038f03f4682e32a52ee

TeX (original user input):

\sigma(a + b) = \sigma(a) + \sigma(b), \quad \sigma(1) = 1, \quad \sigma(a^{-1}) = \sigma(a)^{-1},

TeX (checked):

\sigma (a+b)=\sigma (a)+\sigma (b),\quad \sigma (1)=1,\quad \sigma (a^{-1})=\sigma (a)^{-1},

LaTeXML (experimental; uses MathML) rendering

MathML (10.354 KB / 1.414 KB) :

σ ( a + b ) = σ ( a ) + σ ( b ) , σ ( 1 ) = 1 , σ ( a - 1 ) = σ ( a ) - 1 , formulae-sequence 𝜎 𝑎 𝑏 𝜎 𝑎 𝜎 𝑏 formulae-sequence 𝜎 1 1 𝜎 superscript 𝑎 1 𝜎 superscript 𝑎 1 {\displaystyle\sigma(a+b)=\sigma(a)+\sigma(b),\quad\sigma(1)=1,\quad\sigma(a^{% {-1}})=\sigma(a)^{{-1}},}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle\sigma(a+b)=\sigma(a)+\sigma(b),\quad\sigma(1)=1,\quad\sigma(a^{%&#10;{-1}})=\sigma(a)^{{-1}},}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.39">
      <mrow id="p1.1.m1.1.39.2" xref="p1.1.m1.1.39.2.1.cmml">
        <mrow id="p1.1.m1.1.39.2.2" xref="p1.1.m1.1.39.2.2.cmml">
          <mrow id="p1.1.m1.1.39.2.2.1" xref="p1.1.m1.1.39.2.2.1.cmml">
            <mi id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml">σ</mi>
            <mo id="p1.1.m1.1.39.2.2.1.1" xref="p1.1.m1.1.39.2.2.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.39.2.2.1.2" xref="p1.1.m1.1.39.2.2.1.2.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.2" xref="p1.1.m1.1.39.2.2.1.2.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.39.2.2.1.2.2" xref="p1.1.m1.1.39.2.2.1.2.2.cmml">
                <mi id="p1.1.m1.1.3" xref="p1.1.m1.1.3.cmml">a</mi>
                <mo id="p1.1.m1.1.4" xref="p1.1.m1.1.4.cmml">+</mo>
                <mi id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">b</mi>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.6" xref="p1.1.m1.1.39.2.2.1.2.2.cmml">)</mo>
            </mrow>
          </mrow>
          <mo id="p1.1.m1.1.7" xref="p1.1.m1.1.7.cmml">=</mo>
          <mrow id="p1.1.m1.1.39.2.2.2" xref="p1.1.m1.1.39.2.2.2.cmml">
            <mrow id="p1.1.m1.1.39.2.2.2.1" xref="p1.1.m1.1.39.2.2.2.1.cmml">
              <mi id="p1.1.m1.1.8" xref="p1.1.m1.1.8.cmml">σ</mi>
              <mo id="p1.1.m1.1.39.2.2.2.1.1" xref="p1.1.m1.1.39.2.2.2.1.1.cmml"></mo>
              <mrow id="p1.1.m1.1.39.2.2.2.1.2" xref="p1.1.m1.1.39.2.2.2.1.cmml">
                <mo stretchy="false" id="p1.1.m1.1.9" xref="p1.1.m1.1.39.2.2.2.1.cmml">(</mo>
                <mi id="p1.1.m1.1.10" xref="p1.1.m1.1.10.cmml">a</mi>
                <mo stretchy="false" id="p1.1.m1.1.11" xref="p1.1.m1.1.39.2.2.2.1.cmml">)</mo>
              </mrow>
            </mrow>
            <mo id="p1.1.m1.1.12" xref="p1.1.m1.1.12.cmml">+</mo>
            <mrow id="p1.1.m1.1.39.2.2.2.2" xref="p1.1.m1.1.39.2.2.2.2.cmml">
              <mi id="p1.1.m1.1.13" xref="p1.1.m1.1.13.cmml">σ</mi>
              <mo id="p1.1.m1.1.39.2.2.2.2.1" xref="p1.1.m1.1.39.2.2.2.2.1.cmml"></mo>
              <mrow id="p1.1.m1.1.39.2.2.2.2.2" xref="p1.1.m1.1.39.2.2.2.2.cmml">
                <mo stretchy="false" id="p1.1.m1.1.14" xref="p1.1.m1.1.39.2.2.2.2.cmml">(</mo>
                <mi id="p1.1.m1.1.15" xref="p1.1.m1.1.15.cmml">b</mi>
                <mo stretchy="false" id="p1.1.m1.1.16" xref="p1.1.m1.1.39.2.2.2.2.cmml">)</mo>
              </mrow>
            </mrow>
          </mrow>
        </mrow>
        <mo rspace="12.5pt" id="p1.1.m1.1.17" xref="p1.1.m1.1.39.2.1a.cmml">,</mo>
        <mrow id="p1.1.m1.1.39.2.3" xref="p1.1.m1.1.39.2.3.1.cmml">
          <mrow id="p1.1.m1.1.39.2.3.2" xref="p1.1.m1.1.39.2.3.2.cmml">
            <mrow id="p1.1.m1.1.39.2.3.2.1" xref="p1.1.m1.1.39.2.3.2.1.cmml">
              <mi id="p1.1.m1.1.19" xref="p1.1.m1.1.19.cmml">σ</mi>
              <mo id="p1.1.m1.1.39.2.3.2.1.1" xref="p1.1.m1.1.39.2.3.2.1.1.cmml"></mo>
              <mrow id="p1.1.m1.1.39.2.3.2.1.2" xref="p1.1.m1.1.39.2.3.2.1.cmml">
                <mo stretchy="false" id="p1.1.m1.1.20" xref="p1.1.m1.1.39.2.3.2.1.cmml">(</mo>
                <mn id="p1.1.m1.1.21" xref="p1.1.m1.1.21.cmml">1</mn>
                <mo stretchy="false" id="p1.1.m1.1.22" xref="p1.1.m1.1.39.2.3.2.1.cmml">)</mo>
              </mrow>
            </mrow>
            <mo id="p1.1.m1.1.23" xref="p1.1.m1.1.23.cmml">=</mo>
            <mn id="p1.1.m1.1.24" xref="p1.1.m1.1.24.cmml">1</mn>
          </mrow>
          <mo rspace="12.5pt" id="p1.1.m1.1.25" xref="p1.1.m1.1.39.2.3.1a.cmml">,</mo>
          <mrow id="p1.1.m1.1.39.2.3.3" xref="p1.1.m1.1.39.2.3.3.cmml">
            <mrow id="p1.1.m1.1.39.2.3.3.1" xref="p1.1.m1.1.39.2.3.3.1.cmml">
              <mi id="p1.1.m1.1.27" xref="p1.1.m1.1.27.cmml">σ</mi>
              <mo id="p1.1.m1.1.39.2.3.3.1.1" xref="p1.1.m1.1.39.2.3.3.1.1.cmml"></mo>
              <mrow id="p1.1.m1.1.39.2.3.3.1.2" xref="p1.1.m1.1.39.2.3.3.1.2.2.cmml">
                <mo stretchy="false" id="p1.1.m1.1.28" xref="p1.1.m1.1.39.2.3.3.1.2.2.cmml">(</mo>
                <msup id="p1.1.m1.1.39.2.3.3.1.2.2" xref="p1.1.m1.1.39.2.3.3.1.2.2.cmml">
                  <mi id="p1.1.m1.1.29" xref="p1.1.m1.1.29.cmml">a</mi>
                  <mrow id="p1.1.m1.1.30.1" xref="p1.1.m1.1.30.1.cmml">
                    <mo id="p1.1.m1.1.30.1.1" xref="p1.1.m1.1.30.1.1.cmml">-</mo>
                    <mn id="p1.1.m1.1.30.1.2" xref="p1.1.m1.1.30.1.2.cmml">1</mn>
                  </mrow>
                </msup>
                <mo stretchy="false" id="p1.1.m1.1.31" xref="p1.1.m1.1.39.2.3.3.1.2.2.cmml">)</mo>
              </mrow>
            </mrow>
            <mo id="p1.1.m1.1.32" xref="p1.1.m1.1.32.cmml">=</mo>
            <mrow id="p1.1.m1.1.39.2.3.3.2" xref="p1.1.m1.1.39.2.3.3.2.cmml">
              <mi id="p1.1.m1.1.33" xref="p1.1.m1.1.33.cmml">σ</mi>
              <mo id="p1.1.m1.1.39.2.3.3.2.1" xref="p1.1.m1.1.39.2.3.3.2.1.cmml"></mo>
              <msup id="p1.1.m1.1.39.2.3.3.2.2" xref="p1.1.m1.1.39.2.3.3.2.2.cmml">
                <mrow id="p1.1.m1.1.39.2.3.3.2.2.2" xref="p1.1.m1.1.39.2.3.3.2.2.cmml">
                  <mo stretchy="false" id="p1.1.m1.1.34" xref="p1.1.m1.1.39.2.3.3.2.2.cmml">(</mo>
                  <mi id="p1.1.m1.1.35" xref="p1.1.m1.1.35.cmml">a</mi>
                  <mo stretchy="false" id="p1.1.m1.1.36" xref="p1.1.m1.1.39.2.3.3.2.2.cmml">)</mo>
                </mrow>
                <mrow id="p1.1.m1.1.37.1" xref="p1.1.m1.1.37.1.cmml">
                  <mo id="p1.1.m1.1.37.1.1" xref="p1.1.m1.1.37.1.1.cmml">-</mo>
                  <mn id="p1.1.m1.1.37.1.2" xref="p1.1.m1.1.37.1.2.cmml">1</mn>
                </mrow>
              </msup>
            </mrow>
          </mrow>
        </mrow>
      </mrow>
      <mo id="p1.1.m1.1.38">,</mo>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.39.2.1.cmml" xref="p1.1.m1.1.39.2">
        <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.1a.cmml" xref="p1.1.m1.1.17">formulae-sequence</csymbol>
        <apply id="p1.1.m1.1.39.2.2.cmml" xref="p1.1.m1.1.39.2.2">
          <eq id="p1.1.m1.1.7.cmml" xref="p1.1.m1.1.7"/>
          <apply id="p1.1.m1.1.39.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.1">
            <times id="p1.1.m1.1.39.2.2.1.1.cmml" xref="p1.1.m1.1.39.2.2.1.1"/>
            <ci id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1">𝜎</ci>
            <apply id="p1.1.m1.1.39.2.2.1.2.2.cmml" xref="p1.1.m1.1.39.2.2.1.2">
              <plus id="p1.1.m1.1.4.cmml" xref="p1.1.m1.1.4"/>
              <ci id="p1.1.m1.1.3.cmml" xref="p1.1.m1.1.3">𝑎</ci>
              <ci id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5">𝑏</ci>
            </apply>
          </apply>
          <apply id="p1.1.m1.1.39.2.2.2.cmml" xref="p1.1.m1.1.39.2.2.2">
            <plus id="p1.1.m1.1.12.cmml" xref="p1.1.m1.1.12"/>
            <apply id="p1.1.m1.1.39.2.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.1">
              <times id="p1.1.m1.1.39.2.2.2.1.1.cmml" xref="p1.1.m1.1.39.2.2.2.1.1"/>
              <ci id="p1.1.m1.1.8.cmml" xref="p1.1.m1.1.8">𝜎</ci>
              <ci id="p1.1.m1.1.10.cmml" xref="p1.1.m1.1.10">𝑎</ci>
            </apply>
            <apply id="p1.1.m1.1.39.2.2.2.2.cmml" xref="p1.1.m1.1.39.2.2.2.2">
              <times id="p1.1.m1.1.39.2.2.2.2.1.cmml" xref="p1.1.m1.1.39.2.2.2.2.1"/>
              <ci id="p1.1.m1.1.13.cmml" xref="p1.1.m1.1.13">𝜎</ci>
              <ci id="p1.1.m1.1.15.cmml" xref="p1.1.m1.1.15">𝑏</ci>
            </apply>
          </apply>
        </apply>
        <apply id="p1.1.m1.1.39.2.3.1.cmml" xref="p1.1.m1.1.39.2.3">
          <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.3.1a.cmml" xref="p1.1.m1.1.25">formulae-sequence</csymbol>
          <apply id="p1.1.m1.1.39.2.3.2.cmml" xref="p1.1.m1.1.39.2.3.2">
            <eq id="p1.1.m1.1.23.cmml" xref="p1.1.m1.1.23"/>
            <apply id="p1.1.m1.1.39.2.3.2.1.cmml" xref="p1.1.m1.1.39.2.3.2.1">
              <times id="p1.1.m1.1.39.2.3.2.1.1.cmml" xref="p1.1.m1.1.39.2.3.2.1.1"/>
              <ci id="p1.1.m1.1.19.cmml" xref="p1.1.m1.1.19">𝜎</ci>
              <cn type="integer" id="p1.1.m1.1.21.cmml" xref="p1.1.m1.1.21">1</cn>
            </apply>
            <cn type="integer" id="p1.1.m1.1.24.cmml" xref="p1.1.m1.1.24">1</cn>
          </apply>
          <apply id="p1.1.m1.1.39.2.3.3.cmml" xref="p1.1.m1.1.39.2.3.3">
            <eq id="p1.1.m1.1.32.cmml" xref="p1.1.m1.1.32"/>
            <apply id="p1.1.m1.1.39.2.3.3.1.cmml" xref="p1.1.m1.1.39.2.3.3.1">
              <times id="p1.1.m1.1.39.2.3.3.1.1.cmml" xref="p1.1.m1.1.39.2.3.3.1.1"/>
              <ci id="p1.1.m1.1.27.cmml" xref="p1.1.m1.1.27">𝜎</ci>
              <apply id="p1.1.m1.1.39.2.3.3.1.2.2.cmml" xref="p1.1.m1.1.39.2.3.3.1.2">
                <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.3.3.1.2.2.1.cmml" xref="p1.1.m1.1.39.2.3.3.1.2">superscript</csymbol>
                <ci id="p1.1.m1.1.29.cmml" xref="p1.1.m1.1.29">𝑎</ci>
                <apply id="p1.1.m1.1.30.1.cmml" xref="p1.1.m1.1.30.1">
                  <minus id="p1.1.m1.1.30.1.1.cmml" xref="p1.1.m1.1.30.1.1"/>
                  <cn type="integer" id="p1.1.m1.1.30.1.2.cmml" xref="p1.1.m1.1.30.1.2">1</cn>
                </apply>
              </apply>
            </apply>
            <apply id="p1.1.m1.1.39.2.3.3.2.cmml" xref="p1.1.m1.1.39.2.3.3.2">
              <times id="p1.1.m1.1.39.2.3.3.2.1.cmml" xref="p1.1.m1.1.39.2.3.3.2.1"/>
              <ci id="p1.1.m1.1.33.cmml" xref="p1.1.m1.1.33">𝜎</ci>
              <apply id="p1.1.m1.1.39.2.3.3.2.2.cmml" xref="p1.1.m1.1.39.2.3.3.2.2">
                <csymbol cd="ambiguous" id="p1.1.m1.1.39.2.3.3.2.2.1.cmml" xref="p1.1.m1.1.39.2.3.3.2.2">superscript</csymbol>
                <ci id="p1.1.m1.1.35.cmml" xref="p1.1.m1.1.35">𝑎</ci>
                <apply id="p1.1.m1.1.37.1.cmml" xref="p1.1.m1.1.37.1">
                  <minus id="p1.1.m1.1.37.1.1.cmml" xref="p1.1.m1.1.37.1.1"/>
                  <cn type="integer" id="p1.1.m1.1.37.1.2.cmml" xref="p1.1.m1.1.37.1.2">1</cn>
                </apply>
              </apply>
            </apply>
          </apply>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle\sigma(a+b)=\sigma(a)+\sigma(b),\quad\sigma(1)=1,\quad\sigma(a^{%
{-1}})=\sigma(a)^{{-1}},}</annotation>
  </semantics>
</math>

SVG (10.607 KB / 2.618 KB) :

sigma times left-parenthesis a plus b right-parenthesis equals sigma times left-parenthesis a right-parenthesis plus sigma times left-parenthesis b right-parenthesis comma sigma times left-parenthesis 1 right-parenthesis equals 1 comma sigma times left-parenthesis a Superscript negative 1 Baseline right-parenthesis equals sigma times left-parenthesis a right-parenthesis Superscript negative 1 Baseline comma

MathML with SVG or PNG fallback (recommended for modern browsers and accessibility tools) rendering

MathML (0 B / 8 B) :

SVG image empty. Force Re-Rendering

SVG (0 B / 8 B) :


PNG (0 B / 8 B) :


Translations to Computer Algebra Systems

Translation to Maple

In Maple: sigma*(a + b)= sigma*(a)+ sigma*(b), sigma*(1)= 1 , sigma*((a)^(- 1))= sigma*(a)^(- 1),

Information about the conversion process:


Translation to Mathematica

In Mathematica: \[Sigma]*(a + b)= \[Sigma]*(a)+ \[Sigma]*(b), \[Sigma]*(1)= 1 , \[Sigma]*((a)^(- 1))= \[Sigma]*(a)^(- 1),

Information about the conversion process:


Similar pages

Calculated based on the variables occurring on the entire Hua's identity page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results